Prejudice : the target's perspective - Swim, Janet K.; Stangor, Charles (Academic Press, 1998)
This book turns the tables on the way prejudice has been looked at in the past. Almost all of the current information on prejudice focuses on the person holding prejudiced beliefs. This book, however, provides the first summary of research focusing on the intended victims of prejudice. Divided into three sections, the first part discusses how people identify prejudice, what types of prejudice they encounter, and how people react to this prejudice in interpersonal and intergroup settings. The second section discusses the effect of prejudice on task performance, assessment of ones own abilities,